PENERAPAN USHUL AN-NAHW DALAM PENYUSUNAN MATERI PEMBELAJARAN NAHW PEDAGOGIS - Luthfi, Khabibi Muhammad (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2016)
The study of Arabic syntax and the foundation is essentially in the Arab world there is a group that reconstruct the foundation in order to prepare syntactic and group developing pedagogical syntax essentially Arab and foundation combined with Western linguistics, but do not link it with language learning. This article would describe the concept of syntax as a basic foundation of Arabic linguistics epistemology that could be the basis of linguistic pedagogical education in Arabic. Furthermore, this article would identify its application in the preparation of teaching materials for students of pedagogical syntax Indonesia. While the study of Arabic syntax and essentially foundation in Indonesia, many educational institutions Arabic ignore their correlation. Based on linguistic approach to educational and library data analyzed by the text of discourse found that the basic foundation of Arabic syntax is the sama', qiyas, ijma', ta'lil, ta'wil, istihsan 'amil and istishhab. The application of the basic foundation of syntax as the basis for the preparation of learning materials is a pedagogical syntactic analysis of the basic foundations of syntax in generating syntax, allowance rules of syntax, classification of syntactic descriptive elements, comparing element with Indonesian and Arabic syntax and arrrange the teaching materials.